Stanisław Wyspianski’s Dramas on the Polish Theatre Stagesin Vilnius at the Beginning of the 20th c. - Fedorovič, Irena (Slavistica Vilnensis, 2017)
The works of a well-known poet and dramatist Stanisław Wyspiański (1867–1907) were performed in Vilnius theatres some years after the theatrical events in his native Krakow. The first drama written by this author, the shortened version of The Wedding (Wesele) was staged (on the 19th and 22nd of April, 1906) in Vilnius by the ensemble of Józef Puchniewski. During the summer season, on the 22nd of July 1906, the troupe from Kalisz, conducted by Stanisław Knake-Zawadzki, staged two pieces (a full version, without cuts) of the play Wesele. After a break, the most famous of Wyspianski’s plays was staged by the group conducted by Nuna (Antonina) Młodziejowska, the director of Polish Theatre in Vilnius. (the premiere was held on the 10th of November, 1907). They were staging this play until the end of their cultural activity in Vilnius (the 13th of March, 1910). In December 1907, the message about Wyspiański’s death was delivered to Vilnius. The Młodziejowska ensemble prepared a prapremiere of The Judges (Sędziowie), another play by Wyspiański. This drama was in repertoire of the Polish Theatre in Vilnius during the two years of their activity, until the 18th of February, 1910. Other Wyspiański’s plays, except for the Wesele and Sędziowie, were performed on the stages of Vilnius a few years later. In February, 1911, the ensemble of Bronisław Oranowski staged the play Bolesław Śmiały. The other group, managed by Józef Popławski and Julian Strycharski, again staged the play Wesele in the circus pavilion at Lukiski Square (15th of November, 1911), a year later – the play Warszawianka was put on stage by Ferdynand Ruszczyc (premiere 23rd of October, 1912). The same play, Warszawianka, was staged again on the 30th of November, 1913 in a newly rebuilt theatre in the Pohulanka in commemoration of the 6th anniversary of Wyspiański death. Wyspiański’s works were in the repertoire of the theatre in Pohulanka from the Autumn of 1919 (excerpts from Zygmunt August and Legion), and, from January, 1921, the previously mentioned plays (Warszawianka, Sędziowie) were also staged in the Lutnia Theatre, conducted by Franciszek Rychłowski.